APOE-ε4 Carrier Status and Gut Microbiota Dysbiosis in Patients With Alzheimer Disease - Hou, Min; Xu, Gaolian; Ran, Maosheng; Luo, Wei; Wang, Hui (Frontiers in Neuroscience, 2021)
Background Alternations in gut microbiota and a number of genes have been implicated as risk factors for the development of Alzheimer disease (AD). However, the interactions between the altered bacteria and risk genetic variants remain unclear. Objective We aimed to explore associations of the risk genetic variants with altered gut bacteria in the onset of AD. Methods We collected baseline data and stool and blood samples from 30 AD patients and 47 healthy controls in a case-control study. The rs42358/rs4512 (ApoE), rs3851179 (PICALM), rs744373 (BIN1), rs9331888 (CLU), rs670139 (MS4A4E), rs3764650 (ABCA7), rs3865444 (CD33), rs9349407 (CD2AP), rs11771145 (EPHA1), and rs3818361/rs6656401 (CR1) were sequenced, and microbiota composition was characterized using 16S rRNA gene sequencing. The associations of the altered gut bacteria with the risk genetics were analyzed. Results Apolipoprotein ε4 allele and rs744373 were risk loci for the AD among 12 genetic variants. Phylum Proteobacteria; orders Enterobacteriales, Deltaproteobacteria, and Desulfovibrionales; families Enterobacteriaceae and Desulfovibrionaceae; and genera Escherichia–Shigella, Ruminococcaceae_UCG_002, Shuttleworthia, Anaerofustis, Morganelia, Finegoldia, and Anaerotruncus were increased in AD subjects, whereas family Enterococcaceae and genera Megamonas, Enterococcus, and Anaerostipes were more abundant in controls (P < 0.05). Among the altered microbiota, APOE ε4 allele was positively associated with pathogens: Proteobacteria. Conclusion The interaction of APOE ε4 gene and the AD-promoting pathogens might be an important factor requiring for the promotion of AD. Targeting to microbiota might be an effective therapeutic strategy for AD susceptible to APOE ε4 allele. This needs further investigation.